The abortion divide: Exploring the role of exclusion, loss of significance and identity in the radicalization process - Knapton, Holly; Renström, Emma; Lindén, Magnus (Frontiers in Psychology, 2022)
Recent changes in legislation have brought the abortion debate back into the spotlight in the USA and concerns that radical acts may see an upsurge from both sides of the abortion debate have been expressed. Increasing salience regarding one’s position on the issue, may result in feelings of exclusion and isolation in individuals living in states that mismatch their own opinion, given belongingness concerns occur when individuals are in the numerical minority of a group. Social exclusion has been shown to be a motivator in the radicalization process, given it is suggested to be a trigger of significance loss. The significance quest theory of radicalization argues following a loss of significance individuals will be motivated to restore it and identifying with an extreme group may be one outlet to do so. The aim of this paper is to explore how individuals in a numerical minority may experience feelings of exclusion and significance loss and how this may drive radicalization. A quasi-experimental design in the backdrop of the US abortion debate explored how minority group status based on abortion stance resulted in feelings of exclusion and drove a pathway to radicalization. Our findings showed that those in the numerical minority did show feelings of exclusion and were more willing to engage and endorse radical actions compared to those in the majority. Further, serial mediation analysis revealed the pathway between minority group status and engagement and endorsement of extreme actions was fully mediated by need-threat and ingroup identity levels.